Misdiagnosis of interstitial pregnancy followed by circlage operation and failed induced midtrimester abortion: a case report - Sharma, Nalini; Saha, Anusmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Interstitial pregnancy is rare form of ectopic pregnancy that can expand up to 18 weeks leads to massive haemoperitoneum hence early diagnosis is imperative to decrease mortality and morbidity. Present case diagnosed as interstitial pregnancy at laparotomy when she had taken for hysterotomy after two failed courses of medical abortion. Clinicians should bear in mind the limitations of various investigations and should have a higher degree of suspicion for interstitial pregnancy Any deviation from normal response to administration of medical abortificient, such as failure to abort, should instigate the diagnosis of ectopic (interstitial) pregnancy by expert radiologist.